Updates on FIGO Staging Classification and the New WHO Classification for Cancer of the Ovary (Bangladesh Journal of Obstetrics & Gynaecology, 2017)
Background: The knowledge of different subtypes of ovarian cancer is improving with the progress in molecular pathological research. The WHO classification was revised,in parallel with the implementation of the new FIGO staging classification. The former is mainly based on the histopathological findings and defines the actual type of tumor. It has an important impact on prognosis and therapy of the patient.Materials and methods: FIGO staging classification for cancer of the ovary, fallopian tube, and peritoneum published by Jaime Prat and the new WHO Classification of Ovarian Cancer published by Robert Kurman and coauthors in 2014 are summarized.Results: The International Federation of Gynecology and Obstetrics recently significantly revised staging criteria for cancer of the ovary. The latest revision was based on the concept that high-grade serous tubal intraepithelial carcinoma (STIC) may be the origin of some high-grade serous carcinomas of the ovary and peritoneum. Therefore, staging criteria for the ovary, fallopian tube, and peritoneum have been unified. Understanding this background and other important revised points are essential. The previous focus of mesothelial origin of ovarian cancer has been eliminated in new classification. Instead, a discussion of tubal carcinogenesis of hereditary and some other high-grade serous carcinomas is featured. Regarding serous cancers, the previously assumed pathogenesis pathway may be correct for some, but not for all. The earlier transitional cell type of ovarian cancer has been removed while seromucinous tumors have been added as a new entity. The role of some borderline tumors as one possible step in the progression from benign to invasive lesions is incorporated. The article summarizes the essential updates concerning serous, mucinous, seromucinous, endometrioid, clearcell, and Brenner tumors.Conclusion: The new WHO classification takes into account the recent findings on the origin, pathogenesis, and prognosis of different ovarian cancer subtypes. In both FIGO and WHO classification, the tubal origin of hereditary and some non-hereditary high-grade serous cancers is mentioned in contrast to the hitherto theory of mesothelial origin of tumors. Seromucinous tumors represent a new entity.Bangladesh J Obstet Gynaecol, 2017; Vol. 32(1): 33-41